Propylphosphonic acid anhydride–mediated amidation of Morita–Baylis–Hillman–derived indolizine-2-carboxylic acids. Issue 7 (July 2021) - Sekgota, Khethobole C; Isaacs, Michelle; Hoppe, Heinrich C; Seldon, Ronnett; Warner, Digby F; Khanye, Setshaba D; Kaye, Perry T
Propylphosphonic acid anhydride has been successfully used as a coupling agent in the synthesis of a series of indolizine-2-carboxamido derivatives from indolizine-2-carboxylic acid and its 3-acetylated analogue. The acid substrates were obtained by saponification of the corresponding methyl esters produced, in turn, selectively and efficiently, by time-controlled cyclisation of a single Morita–Baylis–Hillman adduct. Various amino and hydrazino compounds with medicinal potential have been used to prepare indolizine-2-carboxamido and hydrazido derivatives.